Carbon Transfer from the Host Diatom Enables Fast Growth and High Rate of N2 Fixation by Symbiotic Heterocystous Cyanobacteria - Keisuke Inomura; Christopher L. Follett; Takako Masuda; Meri Eichner; Ondřej Prášil; Curtis Deutsch (Plants, 2020)
Diatom−diazotroph associations (DDAs) are symbioses where trichome-forming cyanobacteria support the host diatom with fixed nitrogen through dinitrogen (N2) fixation. It is inferred that the growth of the trichomes is also supported by the host, but the support mechanism has not been fully quantified. Here, we develop a coarse-grained, cellular model of the symbiosis between Hemiaulus and Richelia (one of the major DDAs), which shows that carbon (C) transfer from the diatom enables a faster growth and N2 fixation rate by the trichomes. The model predicts that the rate of N2 fixation is 5.5 times that of the hypothetical case without nitrogen (N) transfer to the host diatom. The model estimates that 25% of fixed C from the host diatom is transferred to the symbiotic trichomes to support the high rate of N2 fixation. In turn, 82% of N fixed by the trichomes ends up in the host. Modeled C fixation from the vegetative cells in the trichomes supports only one-third of their total C needs. Even if we ignore the C cost for N2 fixation and for N transfer to the host, the total C cost of the trichomes is higher than the C supply by their own photosynthesis. Having more trichomes in a single host diatom decreases the demand for N2 fixation per trichome and thus decreases their cost of C. However, even with five trichomes, which is about the highest observed for Hemiaulus and Richelia symbiosis, the model still predicts a significant C transfer from the diatom host. These results help quantitatively explain the observed high rates of growth and N2 fixation in symbiotic trichomes relative to other aquatic diazotrophs.